Injectable nanoparticle-loaded hydrogel system for local delivery of sodium alendronate - Posadowska, Urszula; Pařízek, Martin; Filová, Elena; Wlodarczyk-Biegun, Malgorzata; Kamperman, Marleen; Bačáková, Lucie; Pamula, Elzbieta (International journal of pharmaceutics, 2015)
Systemic administration of bisphosphonates, e.g. sodium alendronate (Aln) is characterized by extremely low bioavailability and high toxicity. To omit aforementioned drawbacks an injectable system for the intra-bone delivery of Aln based on Aln-loaded nanoparticles (NPs-Aln) suspended in a hydrogel matrix (gellan gum, GG) was developed. Aln was encapsulated in poly(lactide-co-glycolide) (PLGA 85:15) by solid-oil-water emulsification. Drug release tests showed that within 25 days all the encapsulated drug was released from NPs-Aln and the release rate was highest at the beginning and decreased with time. In contrast, by suspending NPs-Aln in a GG matrix, the release rate was significantly lower and more constant in time. The GG-NPs-Aln system was engineered to be easily injectable and was able to reassemble its structure after extrusion as shown by rheological measurements. Invitro studies showed that the GG-NPs-Aln was cytocompatible with MG-63 osteoblast-like cells and it inhibited RANKL-mediated osteoclastic differentiation of RAW 264.7 cells. The injectability, the sustained local delivery of small doses of Aln and the biological activity render the GG-NPs-Aln system promising for the local treatment of osteoporosis and other bone tissue disorders.
Keywords: farmaceutická chemie; injekce; RAW 264.7 Cells; Animals; Polysaccharides, Bacterial; Kinetics; Cell Line, Tumor; osteoblasty; Lactic Acid; Nanoparticles; kyselina mléčná; Drug Carriers; Osteoclasts; buněčná diferenciace; lidé; Chemistry, Pharmaceutical; Rheology; Hydrogels; Mice; Injections; Solubility; rozpustnost; nanočástice; Bone Density Conservation Agents; myši; osteoklasty; farmaceutická technologie; bakteriální polysacharidy; reologie; Osteoblasts; kyselina polyglykolová; RAW 264.7 buňky; Polyglycolic Acid; hydrogely; Alendronate; nosiče léků; inhibitory kostní resorpce; Cell Differentiation; Nanotechnology; nanotechnologie; zvířata; RANK Ligand; ligand RANK; kinetika; alendronát; nádorové buněčné linie; Technology, Pharmaceutical; Humans